Wrist arthrodesis with the medial femoral condyle flap: Outcomes of vascularized bone grafting for osteomyelitis. Issue 1 (3rd September 2018) - Mattos, David; Ko, Jason H.; Iorio, Matthew L.
Abstract : Background: Osteomyelitis of the wrist is rare but destructive. Subsequent bone defects often require vascularized bone for successful healing. Recent literature has pointed to the successful use of the medial femoral condylar (MFC) flap for difficult non‐unions, yet it has not been specifically described for wrist fusion. We present our experience with this technique for limited and complete wrist arthrodesis. Patients and Methods: We reviewed 4 cases of radiocarpal bone loss from osteomyelitis. All cases utilized debridement of nonviable tissues, and at least 6 weeks of intravenous antibiotics, followed by vascularized bone grafting with a MFC flap. The flap was based on the horizontal periosteal branch of the descending geniculate artery, and utilized to directly bridge the bony defects following resection. Results: Three patients healed primarily, and 1 patient required secondary cancellous bone grafting to reach union. One patient required revision of the donor site closure. None of the patients had a recurrence of infection or other complications. Average follow up was 8.5 months after reconstruction. Average time to union was 11.5 weeks. Three patients demonstrated full composite fist, and 1 patient had incomplete finger range of motion following several flexor and extensor tendon grafts. Conclusions: These cases illustrate the use of the MFC in wrist arthrodesis after osteomyelitis defects. In all cases, there was complete union in a short time, no recurrence of infection, and low donor‐site morbidity.